2018
DOI: 10.2340/00015555-3058
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Ablative CO2 Laser Followed by Topical Application of Sodium Stibogluconate for Treatment of Active Cutaneous Leishmaniasis: A Randomized Controlled Trial

Abstract: SIGNIFICANCE Cutaneous leishmaniasis is a parasitic infection that affects millions of people every year (1). Although common treatments vary in safety and efficacy, none of them addresses the disfiguring atrophic hypo-or hyper-pigmented post-inflammatory scars. The current study shows that fractional carbon dioxide (CO 2) laser treatment, followed by topical application of sodium stibogluconate, is an effective, safe treatment, which is less painful and results in better final cosmesis compared with the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…A number of experimental local treatments such as infiltration with hypertonic salt solutions [ 121 ], trichloroacetic acid [ 122 ], intralesional metronidazole [ 123 ], diphencyprone [ 124 ], carbon dioxide laser [ 125 ], intense pulsed light [ 126 ], photodynamic therapy [ 127 ], and systemic treatments such as cimetidine [ 128 ] in combination with antimoniate and chloroquine [ 129 , 130 ] have been tried in small single-centered studies with varying results that need further evidence to conclude on their therapeutic value.…”
Section: Treatmentmentioning
confidence: 99%
“…A number of experimental local treatments such as infiltration with hypertonic salt solutions [ 121 ], trichloroacetic acid [ 122 ], intralesional metronidazole [ 123 ], diphencyprone [ 124 ], carbon dioxide laser [ 125 ], intense pulsed light [ 126 ], photodynamic therapy [ 127 ], and systemic treatments such as cimetidine [ 128 ] in combination with antimoniate and chloroquine [ 129 , 130 ] have been tried in small single-centered studies with varying results that need further evidence to conclude on their therapeutic value.…”
Section: Treatmentmentioning
confidence: 99%
“…CO 2 lattice laser has strong penetrability, which can precisely control the depth of skin penetration and punctate exfoliation ( Wenande et al, 2017 ). Additionally, CO 2 laser surgery is less invasive and causes reduced trauma and pain ( Artzi et al, 2019 ). Recent studies indicated that its thermal effect can inhibit fungi, initiate local immune responses, and assist the absorption of drugs ( Orringer et al, 2010 ; Sobhi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, since 2012, CO 2 fractional laser‐assisted drug delivery and its combination with drug therapy has appeared in the literature, such as CO 2 fractional laser use with botulinum toxin to treat crow's feet, 59,60 CO 2 fractional laser‐assisted transmission of ascorbic acid, 61 and its combination with triamcinolone acetonide for keloids and hypertrophic scars 62 . In recent years, CO 2 fractional laser has recently been applied as main and adjunctive treatments for a wide range of skin diseases, including cutaneous leishmaniasis, 63,64 adjuvant photodynamic therapy for toenail onychomycosis, 65 basal cell carcinoma, 66 Bowen's disease, 67 non‐melanoma skin cancer, 68 alopecia areata, 55 skin amyloidosis, 69 and acanthosis nigricans 70 . The experimental results show good application prospects worthy of further exploration and research.…”
Section: Application Trends and Future Researchmentioning
confidence: 99%
“…The detailed keywords are further shown in Figure 8.acetonide for keloids and hypertrophic scars. 62 recent years, CO 2 fractional laser has recently been applied as main and adjunctive treatments for a wide range of skin diseases, including cutaneous leishmaniasis,63,64 adjuvant photodynamic therapy for toenail onychomycosis,65 basal cell carcinoma,66 Bowen's disease,67 nonmelanoma skin cancer, 68 alopecia areata, 55 skin amyloidosis,69 and acanthosis nigricans 70. The experimental results show good application prospects worthy of further exploration and research.Large-scale controlled trials with long-term follow-up are still lacking in clinical studies of CO 2 fractional laser, and its therapeutic effects on a variety of diseases need to be demonstrated in more clinical trials.…”
mentioning
confidence: 94%